"Water‐in‐Deep Eutectic Solvent" Electrolytes for High‐Performance Aqueous Zn‐Ion Batteries. (15th April 2021) - Shi, Jinqiang; Sun, Tianjiang; Bao, Junquan; Zheng, Shibing; Du, Haihui; Li, Lin; Yuan, Xuming; Ma, Tao; Tao, Zhanliang
Abstract: Aqueous Zn‐ion batteries have been considered as promising alternatives to Li‐ion batteries due to their abundant reserves, low price, and high safety. However, Zn anode shows poor reversibility and cycling stability in most conventional aqueous electrolytes. Here, a new type of aqueous Zn‐ion electrolyte based on ZnCl2 –acetamide deep eutectic solvent with both environmental and economic friendliness has been prepared. The water molecule introduced in the "water‐in‐deep eutectic solvent" electrolyte could reduce the Zn 2+ desolvation energy barrier by regulating Zn 2+ solvation structure to promote uniform Zn nucleation. Zn anode shows improved electrochemical performance (≈98% Coulombic efficiency over 1000 cycles) in the electrolyte whose molar ratio of ZnCl2 :acetamide:H2 O is 1:3:1. The assembled full battery composed of phenazine cathode and Zn anode could stably cycle over 10 000 cycles with a high capacity retention of 85.7%. Overall, this work offers new insights into exploring new green electrolyte systems for Zn‐ion batteries. Abstract : The "water‐in‐deep eutectic solvent" electrolyte based on ZnCl2, acetamide, and water with both environmental and economic friendliness can induce uniform Zn nucleation by modulating Zn 2+ solvation structure to achieve the fast reaction kinetics on the interface between the electrolyte and Zn metal, accounting for the improved reversibility and cycling stability of the Zn anode.